Analisis Keterkaitan Panjang dan Lebar Langkah dengan Kecepatan Berjalan - Safarina, Lina; Triawati, Aini; Sesanelvira, Meivi; Suharjiman, Suharjiman (Journal of Telenursing (JOTING), 2023)
This study aims to determine the relationship between stride length, stride width, and walking speed on the risk of falls in older people at the Tresna Werdha Tulus Kasih Dan Budi Pertiwi Social Home, Bandung City. The method used is an analytical survey with a cross-sectional research design. The study showed a relationship between step length and the risk of falling, p-value = 0.002 (p ≤ 0.05). There is a relationship between step width and fall risk, p-value = 0.002 (p ≤ 0.05). There is a relationship between walking speed and the risk of falling, p-value = 0.002 (p ≤ 0.05). In conclusion, stride length, width, and walking speed are physical factors that influence the body's balance and coordination. Keywords: Walking Speed, Elderly, Stride Width, Stride Length, Fall Risk